The complete chloroplast genome of Epimedium trifoliolatobinatum (Koidz.) Koidz. (Berberidaceae). Issue 6 (3rd June 2022) - Zhang, Yixin; Liu, Xiang; Zhang, Cheng; Xu, Chaoqun; Suo, Fengmei; Qin, Weihan; Shen, Guoan; Guo, Baolin
Abstract: Epimedium L. is an important genus in the family Berberidaceae. Epimedium trifoliolatobinatum (Koidz.) Koidz. 1939 is inhabited on the west side of the Shikoku, Japan. In this study, the first complete chloroplast genome of E. trifoliolatobinatum was assembled with Illumina paired-end sequencing data, which was 157, 272 bp in length with a total GC content of 38.70%. A total of 112 unique genes were annotated, comprising 78 protein-coding genes, 30 tRNA genes, and four rRNA genes. The phylogenetic analysis suggested that E. trifoliolatobinatum was sister to E. koreanum . The current results provided fundamental information for further conducting molecular systematics and phylogenetic research of Epimedium genus.